Optimizing the Learning with “Smart Learning” for Special Needs Children in Inclusive School: Optimalisasi Pembelajaran dengan “Smart Learning” Untuk Anak Berkebutuhan Khusus di Sekolah Inklusi - Seri Hartati; Nurul Aiyuda; Luluk Elvitaria (Universitas Lancang Kuning, 2023)
This community service was carried out at the inclusive school X in Pekanbaru involving all Children with Special Needs. Children with Special Needs or commonly called ABK is a term for children who have physical, mental, social, or emotional conditions that are different from children in general. The use of the